The Role of Decision-Making Process on Strategic Foreign Direct Investment - Al Halbusi, H. (2015)
This thesis is to uniquely explore the global competition in foreign direct investment [FDI] decision-making processes of Northern Iraq. The Global Competition in Strategic (GCS) in the northern Iraq is uncertain in a global context. GCS is huge in the world and often do not have sufficient resources to fully investigate a major FDI decision. If learning to gain contextual competence is necessary for successful FDI decision-making, how do these firms manage their learning and competencies to invest successfully in the northern Iraq? The main objective of this study addresses the decision-making processes of Global Competition and Strategies for FDI in northern Iraq, how this takes place and how needed competencies are developed and managed.